Evaluation of variants in IL6R, TLR3, and DC-SIGN genes associated with dengue in a sampled Colombian population (2019)
Introduction: Host genetics is recognized as an influential factor for the development of dengue disease. Objective: This study evaluated the association of dengue with the polymorphisms rs8192284 for gene IL6R, rs3775290 for TLR3, and rs7248637 for DC-SIGN. Materials and methods: Of the 292 surveyed subjects, 191 were confirmed for dengue fever and the remaining 101 were included as controls. The genotypes were resolved using polymerase chain reaction and restriction fragment length polymorphism (PCRRFLP). In an attempt to determine the risk (Odds Ratio) of suffering dengue fever, data were analyzed using chi-square for alleles and logistic regression for both genotypes and allelic combinations. Confidence intervals were set to 95% for all tests regardless of the adjustment by either self-identification or ancestry